Maternal BMI, IGF-I Levels, and Birth Weight in African American and White Infants. (2nd June 2013) - Vidal, Adriana C.; Murtha, Amy P.; Murphy, Susan K.; Fortner, Kimberly; Overcash, Francine; Henry, Nikki; Schildkraut, Joellen M.; Forman, Michele R.; Demark-Wahnefried, Wendy; Kurtzberg, Joanne; Jirtle, Randy; Hoyo, Cathrine
Abstract : At birth, elevated IGF-I levels have been linked to birth weight extremes; high birth weight and low birth weight are risk factors for adult-onset chronic diseases including obesity, cardiovascular disease, and type 2 diabetes. We examined associations between plasma IGF-I levels and birth weight among infants born to African American and White obese and nonobese women. Prepregnancy weight and height were assessed among 251 pregnant women and anthropometric measurements of full term infants (≥37 weeks of gestation) were taken at birth. Circulating IGF-I was measured by ELISA in umbilical cord blood plasma. Linear regression models were utilized to examine associations between birth weight and high IGF-I, using the bottom two tertiles as referents. Compared with infants with lower IGF-I levels (≤3rd tertile), those with higher IGF-I levels (>3rd tertile) were 130 g heavier at birth, (β -coefficient = 230, se = 58.0, P = 0.0001 ), after adjusting for gender, race/ethnicity, gestational age, delivery route, maternal BMI and smoking. Stratified analyses suggested that these associations are more pronounced in infants born to African American women and women with BMI ≥30 kg/m 2 ; the cross product term for IGF-I and maternal BMI was statistically significant (P ≤ 0.0004 ). Our findings suggest that the association between IGF-I levels and birth weight depends more on maternal obesity than African American race/ethnicity.